Preparation and Performance of Deep Desulphurization Adsorbent of Heavy Naphtha - Chen, Xia; Li, Feifei; Jin, Jie; Chen, Guangmei (Asian Journal of Chemistry, 2012)
The deep desulphurization adsorbent used on the middle-pressure hydrogenation of heavy naphtha was studied. The results of static adsorption showed that the best components of deep desulphurization adsorbent were Zn/Fe/AT (AT = attapulgite), with the suitable ratio of 2.1:5.4:2.5 (XF-1). Little amount of ammonium carbonate (NC) would be helpful to produce pores, the static sulfur capacity of XF-1-NC was 1.52 × 10-4 g/g, which was 11.7 % higher than that of XF-1.